Boolean Algebra in Computer Science
Boolean Algebra
Boolean theorems are used to simplify Boolean functions in order to use fewer gates. Any variable such as X in binary can have a value of one or zero.
Theorem-1:
[no-highlight]X + X = X
[/no-highlight]
Proof: Select X as 0 then 0+0 = 0, select X = 1 then 1 + 1 = 1 results: X+ X = X
Theorem-2:
[no-highlight]X + 1 = 1
[/no-highlight]
Proof: Select X = 0 then 0+1 = 1, select X = 1 then 1 + 1 = 1, both cases result in 1 then X + 1 = 1
Theorem-3:
[no-highlight]X + 0 = x
[/no-highlight]
Proof: Select X = 0 then 0+0 = 0, select X = 1 then 1 + 0 = 1, result is whatever value X is.
Theorem-4:
[no-highlight]X + X’ = 1
[/no-highlight]
Proof: Select X = 0 then 0+1 = 1, select X = 1 then 1 + 0 = 1, both cases result is 1
Theorem-5:
[no-highlight]X.X = X
[/no-highlight]
Proof: Select X = 1 then 1.1 = 1, select X = 0 then 0.0 = 0, therefore XX=X.
Theorem-6:
[no-highlight]X.1 = X
[/no-highlight]
Proof: Select X = 0 then 1.1 = 1, select X = 0 then 0.1 =0, therefore, X.1 = X.
Theorem-7:
[no-highlight]X.X’ = 0
[/no-highlight]
Proof: Select X = 0 then 0.1 = 1, select X = 1 then 1.0 =0, both values of X result is 0.
Theorem-8:
[no-highlight](X’)’ = X
[/no-highlight]
(0′)’ = (1)’ = 0, (1′)’ = (0)’ = 1 Whatever the value X has.
Distributive Theorem:
[no-highlight]X(Y + Z) = XY + XZ
[/no-highlight]
De Morgan’s Theorem-I:
[no-highlight](X + Y)’ = X’Y’
[/no-highlight]
In this theorem, the OR between X and Y is negated and changes the OR operation to the AND operation.
Proof: By making a truth table for both sides of the theorem, it shows that both sides of the theorem generate the same truth table
De Morgan’s Theorem-II:
[no-highlight](XY)’ = X’ + Y’
[/no-highlight]
In this theorem, the XY is complemented and changes from an AND operation to an OR operation with each component complimented.
If the truth table of both sides were generated, then it would show that both sides have the same truth table result.
Commutative Law:
[no-highlight]X + Y = Y + X
XY = YX
[/no-highlight]
Associative Law:
[no-highlight]X(YZ) = (XY)Z
X + (Y + Z) = (X + Y) + Z
[/no-highlight]